Insufficient CXCL13 secretion in leprosy foamy macrophages attenuates lymphocyte recruitment and antimicrobial protein production - Wang, Chuan; Zhang, Yuan; Liu, Tingting; Mi, Zihao; Shi, Peidian; Wang, Zhenzhen; Li, Wenchao; Wang, Honglei; Liu, Hong; Zhang, Furen (Frontiers in Immunology, 2025)
BackgroundPathogens trigger metabolic reprogramming, leading to the formation of foamy macrophages (FMs). This process provides a favorable environment for bacterial proliferation and enables bacteria to evade immune killing.ObjectiveTo elucidate the mechanisms by which pathogens escape immune surveillance and elimination via the formation of FMs.MethodsWe constructed a FM model using monocyte-derived macrophages (MDMs) that were incubated with oxidized low-density lipoprotein (oxLDL). Subsequently, we employed bulk RNA-sequencing (bulk RNA-seq) to comprehensively analyze the immune responses in MDMs and FMs against Mycobacterium leprae (M. leprae) infection in samples from 10 healthy individuals.ResultsWe found that CXCL13, a component of the cytokine-cytokine receptor interaction pathway, was specifically upregulated in M. leprae infected MDMs, when compared with M. leprae infected FMs. Significantly, further functional analyses revealed that in vitro treatment with CXCL13 could enhance the expression of CXCR5, thereby promoting lymphocyte migration and secretion of antimicrobial proteins. Additionally, NLRP12 was found to be specifically and highly expressed in the NOD-like receptor signaling pathway, which was enriched in infected FMs. In macrophages, M. leprae infection increased CXCL13 expression via NF-κB signal pathway. Conversely, in FMs, mycobacteria induced upregulation of CXCL13 was suppressed by NLRP12 through the inhibition of p52 factor expression.ConclusionIn conclusion, the NLRP12/NF-κB/CXCL13 axis is crucial for the immune response of FMs after mycobacterial infection. These findings contribute to a deeper understanding of the pathological mechanisms of mycobacterial infection.